Which Countries' Citizens Are Better Off With Trade?. (December 2015) - Kosack, Stephen; Tobin, Jennifer L.
Summary: We attempt to reconcile competing arguments regarding international trade's implications for citizen well-being: that trade either erodes citizen welfare by decreasing the incentives and resources for welfare improvements or leads to higher welfare by increasing those incentives and resources. We find that which of these two dynamics a country experiences depends on its level of human capital. In countries already well-endowed with human capital, greater international trade reinforces further improvements in welfare. But in most countries, the workforce has not yet developed such capacities, and in these countries trade is associated with slower improvements in welfare.